A comparative study of financial performance between Bank Islam Malaysia Berhad (BIMB) and Bank Muamalat Malaysia Berhad (BMMB) / Dian Sairini Mohamad Yusu - Mohamad Yusu, Dian Sarini (2007)
The purpose of this study is to examine the financial performance between Bank Islam Malaysia Berhad (BIMB) and Bank Muamalat Malaysia Berhad (BMMB). Other than that, this study identifies the differences between the performance of Bank Islam and Bank Muamalat with financial position indicators. It is also identify the differences and compared the performance in terms of the profitability, liquidity and leverage as well as to find out which banks perform better. Secondary data will be used for this study which covers the period from 1996 to 2006. This study used financial ratios such as profitability, liquidity and leverage to analyze the financial performance between these two banks. The test conducted is Independent Sample T-Test which will tells whether the performance between BIMB and BMMB is equal or not equal. Thus, the overall performance of BIMB is better than BMMB since it is the first Islamic bank in Malaysia and because of that it has many experiences on how to conduct the Islamic banking practices in this country compared to BMMB.